Corporate Social Responsibility Issues in Modern Banking System - MARECKI Krzysztof; GRZYMAŁA Zbigniew; MATUSEWICZ Michał; WÓJCIK-CZERNIAWSKA Agnieszka (Communications of International Proceedings, 2022)
Although the concept of corporate social responsibility isn't unique to the banking business, it has grown more significant in the latest days as the recession has highlighted the significance of implementing moral rules into the financial sector. According to past knowledge with the implementation of CSR and professional ethics in the contemporary banking industry, bank social responsibility and financial services morality are regarded as an advertising component of public interaction and are not incorporated into personal bank lending policy initiatives. Corporate Social Responsibility (CSR) is a strategy for achieving long-term and sustainable economic benefit by responding to large unmet societal needs. The banking sector, in particular, plays a key role in conducting different social and humanitarian programs to assist the country's poor. Banks have concentrated their CSR operations in the areas of the market, workplace, social, and environmental regulation to support their CSR initiatives.
Keywords: Corporate social responsibility; Issues; Cooperation; Banks.